HUBUNGAN TINGKAT KECEMASAN DENGAN KUALITAS TIDUR PADA MAHASISWA INSTITUT KESEHATAN IMMANUEL - Linda; Tanan, Karisma; Sitorus, Neti (Jurnal Ilmu Kesehatan Immanuel, 2024)
Anxiety is a normal symptom in humans, but it can become pathological if the symptoms persist for a certain period of time and disturb the individual's peace of mind. Students are a group that is vulnerable to experiencing anxiety. Anxiety that occurs in teenagers has an impact on sleep quality, such as insomnia, namely difficulty or not being able to sleep. This condition causes many effects, such as reduced concentration in learning and health problems. The aim of the research was to determine the relationship between anxiety levels and sleep quality in Immanuel Health Institute students. This research design uses a cross-sectional approach. The research population consisted of all 825 Immanuel Health Institute students. The total sample was 89 people, and the sampling technique used was proportional random sampling. The research instrument used was the Hamilton Anxiety Rating Scale (HARS) questionnaire and the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The data was analyzed using Chi Square. The research results showed that 44.9% of respondents experienced moderate anxiety, and 65.1% of respondents had poor sleep quality. Chi-square test results show that there is a relationship between anxiety levels and sleep quality with a p value <0.004.